Performance of Broiler Chicken Carcass Provided with Water Extract (Phyllanthus niruri L) and Moringa (Moringa oleifera Lam) - Puji Astuti; Heru Suripta (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
This study aims to determine the performance of broiler carcasses given meniran and moringa extracts. The research was conducted for 28 days at the Animal Husbandry Practice Unit (UPT) of the Karanganyar Animal Husbandry Academy. The material used was 60 broiler strain Ross strains aged 4 days, kept in 12 experimental units, each unit consisting of 5 chickens with an average initial weight of 95.77 ± 4.79 g. The first treatment (T0) control, chicken without giving meniran and moringa extracts, the second treatment (T1) the chicken was given 5 ml meniran extract per liter of drinking water, the third treatment (T2) the chickens were given 2.5 ml meniran extract and moringa 2 extract, 5 Moringa extracts per liter of drinking water, the fourth treatment (T3) of chickens was given Moringa extract 5 ml per liter of drinking water. The variables observed included drinking water consumption, final body weight, carcass weight, carcass percentage, and abdominal fat percentage. The design used was a completely randomized design (CRD). The data were analyzed for variety and if there was a significant effect of the treatment, it was continued with the Duncan Multiple Distance Test to determine differences in treatment. The results showed that drinking water consumption, percentage, and percentage of abdominal fat were not significantly different between treatments, final body weight (g / head / day). , and carcass weight was significantly different between treatments. The conclusion of this research is that giving meniran and moringa extracts in drinking water does not affect the performance of broiler chicken carcasses. Keywords : Moringa meniran extract, final body weight, carcass weight, carcass percentage, abdominal fat percentage